AN OVERVIEW STATUS OF LITERACY AMONG RURAL ANDHRA PRADESH - Kosari, Dr.Ravindra (IJRDO - Journal of Applied Management Science, 2016)
In India, its organization and the progress that has been made Since independence. Differentcomponents that constitute Rural education infrastructure are evaluated for their relative Importance inthe delivery of effective learning. We also examine the current status of rural education infrastructure inthe country and gaps in the provisioning. the education policies of successive governments have built onthe substantial legacies of the Nehruvian period, targeting the core themes of plurality and secularism,with a focus on excellence in higher education, and inclusiveness at all levels. In reaching these goals, theissue of funding has become problematic; governments have promised to increase state spending whilerealizing the economic potential of bringing in private-sector financial support. Paper also focus onCrude Literacy Rate in India by 2011, Literacy rate in Andhra Pradesh of India 2011 and Steps taken bygovernment in accelerating Education planning in India.